Modality in The Grand Campaign Speech of Presidential Candidates of Indonesia 2024 - Triumph Sihombing; Amrin Saragih; Anni Holila Pulungan (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This research deal with types of modality used in the Speech Texts of the Presidential Campaign of the 2024 Indonesian General Elections. The objectives of this research were to analyze and categorize the modality used in the grand campaign speech texts of presidential candidates of the 2024 and to elucidate the realizations of the types of modality whether Modalization or Modulation used in the grand campaign speech texts of presidential candidates of the 2024. The researcher had observed and looked at the speeches of the three candidates of the 2024 presidential election from KOMPASTV news in YouTube, wrote the transcripts of the speeches of the three candidates and identified the modality in the speech. Based on Halliday’s theory about Modality, it could be found in the sentence or clause. It was found that the modulation of obligation at medium levels of modality was the most used in the grand campaign. It was the most dominant feature found among the three candidates, Prabowo Subianto, Anies Baswedan and followed by Ganjar Pranowo. It meant the candidates convinced the voter that the candidates had obligation before the voters’ futures as they used modulation of obligation type in their grand campaign speech.